Green Spectrophotometric Determination of Organophosphate in Selected Fruits and Vegetables - Hemraj Sharma; Hari Prasad Sapkota; Kanchan Paudel; Anusha Raila; Sujata Kandel; Pramod Chaudhary; Kritika Bhattarai (International Journal of Analytical Chemistry)
A simple, sensitive, precise, and environmentally safe spectrophotometry method was developed and validated for the determination of organophosphate in various fruits and vegetables using a UV-Visible spectrophotometer using a magnesia mixture. The volume of reagent used for analysis and the stability of the color complex were also optimized. The drug showed a stable white color complex at 420 nm. The greenness of the methods was estimated using an ecoscale (84), the Green Analytical Procedure Index, and AGREE (0.89), which were found to be excellent green method based on spectrophotometric determination. The method was validated using ICH guidelines and has acceptable values for linearity (0.5–2.5 mg/ml), accuracy (98.5–102.5%), precision, robustness, limit of detection (0.16 mg), and limit of quantification (0.486 mg). The concentration of the organophosphate in the analyzed sample was in the range of 0.003 to 2.45 mg. Altogether, the proposed green analytical method was found to be a simple, selective, sensitive, accurate, and ecofriendly method for the analysis of organophosphate in various fruits and vegetables.